Body uneasiness is associated with food addiction symptoms: A cross‐sectional study. (18th September 2018) - Imperatori, Claudio; Innamorati, Marco; Lamis, Dorian A.; Farina, Benedetto; Fabbricatore, Mariantonietta; Contardi, Anna
Abstract: The main aim of the present study was to investigate the association between food addiction (FA) symptoms and body uneasiness in a nonclinical sample, while controlling for potential confounding variables. Participants ( N = 395; 123 men) were administered self‐report measures assessing FA, binge eating severity, body uneasiness, depressive symptoms, emotion dysregulation and socio‐demographic variables. Body uneasiness was independently associated with FA symptoms (standardized beta coefficients ranging between 0.41 [ p < 0.001] and 0.22 [ p < 0.001]), even when controlling for the presence of other variables. This finding suggests that body uneasiness may be a crucial symptom in the development and/or maintenance of FA symptoms.